Genetic analysis of X-linked hybrid sterility in the house mouse - Storchová, Radka; Gregorová, Sona; Buckiová, Daniela; Kyselová, Vendula; Divina, Petr; Forejt, Jirí (Mammalian genome, 2004)
Hybrid sterility is a common postzygotic reproductive isolation mechanism that appears in the early stages of speciation of various organisms. Mus musculus musculus and Mus musculus domesticus represent two recently separated mouse subspecies particularly suitable for genetic studies of hybrid sterility. Here we show that the introgression of Chr X of M. m. musculus origin (PWD/Ph inbred strain, henceforth PWD) into the genetic background of the C57BL/6J (henceforth B6) inbred strain (predominantly of M. m. domesticus origin) causes male sterility. The X-linked hybrid sterility is associated with reduced testes weight, lower sperm count, and morphological abnormalities of sperm heads. The analysis of recombinant Chr Xs in sterile and fertile males as well as quantitative trait locus (QTL) analysis of several fertility parameters revealed an oligogenic nature of the X-linked hybrid sterility. The Hstx1 locus responsible for male sterility was mapped near DXMit119 in the central part of Chr X. To ensure full sterility, the PWD allele of Hstx1 has to be supported with the PWD allelic form of loci in at least one proximal and/or one distal region of Chr X. Mapping and cloning of Hstx1 and other genes responsible for sterility of B6-X PWD Y B6 males could help to elucidate the special role of Chr X in hybrid sterility and consequently in speciation.
Keywords: Animals; chromozom X; Genotype; Female; Phenotype; genetická vazba; akrozomální reakce; spermie; ženské pohlaví; Testis; Spermatozoa; Acrosome Reaction; Antibodies, Monoclonal; rekombinantní proteiny; Recombinant Proteins; Mice; genotyp; testis; Mice, Inbred BALB C; myši; ženská infertilita; křížení genetické; Sex Factors; Infertility, Male; Male; X Chromosome; Infertility, Female; sexuální faktory; myši inbrední BALB C; Genetic Linkage; Crosses, Genetic; alely; Alleles; monoklonální protilátky; Quantitative Trait Loci; fenotyp; zvířata; genetické markery; mužská infertilita; mužské pohlaví; lokus kvantitativního znaku; Mice, Inbred C57BL; myši inbrední C57BL; Genetic Markers